Pembelajaran Kontekstual Filosofi Ekonomi Cukup - Rizki Listyono Putro; Hari Wahyono; Mit Witjaksono (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2018)
Abstract: This study is aimed to create a learning scenario that intends to introduce the concept dan principal of Sufficiency Economy Philosophy (SEP) based on Pancasila and article 33 of the constitution of Republic of Indonesia (The UUD 1945) and to construct the value of SEP, Pancasila, and article 33 UUD 1945 into the learning process. This study use qualitative approach and use Design Based Research (DBR) as the design of development. The result of this study are (1) create a learning scenario that gives real experiences to students and (2) change of mindset, knowledge and attitude of the high school students in applying SEP, Pancasila and article 33 UUD 1945.